Pengaruh Media Pembelajaran (Moodle Mobile Learning, LKS) dan Minat Peserta Didik terhadap Hasil Belajar Mata Pelajaran Administrasi Server - Mukahar, Achmad (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
This research aimed to 1) measure the effect of learning media utilization and students interest on the learning outcome of server administration subject, 2) find out the impact of the interaction between learning media utilization and students interest on the learning outcome, 3) measure the effect between high learning interest and low learning interest using different learning media on the learning outcome. The research method was a pseudo experiment with 2x2 factorial research design, which meant comparing two groups: experiment group using moodle mobile learning media, and control group using student worksheet and distinguish students interest in low or high. Both groups were given pretest and post-test. The data was obtained through a questionnaire and a formative test. The data processing used two-way ANOVA and SPSS ver. 24 as a processing data aid.